Application of the Game-Based Approach in Optimizing Fundamental Movement Skills in Learning for Junior High School Students - Bagong Yanuar Arif; Advendi Kristiyandaru; Afifan Yulfadinata (Science Education and Application Journal, 2026)
Fundamental Movement Skills (FMS) are essential to students’ motor development and serve as the foundation for participation in various physical activities. However, physical education learning in many junior high schools still relies on teacher-centered instruction and repetitive technical drills, which often limit students’ active engagement and meaningful movement experiences. This study aimed to examine the effectiveness of a game-based learning approach in improving students’ fundamental movement skills in physical education classes. A quasi-experimental one-group pretest–posttest design was employed. The participants were 30 seventh-grade students aged 12–13 years from a public junior high school. The intervention was conducted over four weeks with eight learning sessions using structured game-based activities designed to stimulate locomotor, non-locomotor, and manipulative movements. Fundamental movement skills were assessed using a modified movement skill test adapted for junior high school students. Data were analyzed using descriptive statistics and a paired-sample t-test to determine differences between pretest and posttest scores. The results indicated a significant improvement in students’ fundamental movement skills after the implementation of the game-based learning approach (p < .001). Improvements were observed across locomotor, non-locomotor, and manipulative movement components. In addition to motor improvement, students demonstrated higher participation and engagement during physical education lessons. These findings suggest that game-based learning can provide meaningful movement experiences and effectively support the development of fundamental movement skills among junior high school students. Therefore, integrating game-based activities into physical education lessons is recommended to enhance both motor competence and student engagement.